Photocatalytic Degradation of Nonionic Surfactant Using Zinc Oxide Nanoparticles - Giahi, M.; Ghanbari, F.; Issazadeh, K. (Asian Journal of Chemistry, 2013)
In this paper, the photocatalytic degradation of nonylphenol polyethoxylate (10 ethylene oxide units, NP10EO), a nonionic surfactant, was investigated in aqueous solution using ZnO nanoparticles. The degradation was studied under different conditions such as the amount of photocatalyst, illumination time, reaction temperature and initial concentration, presence of electron acceptor. The results showed that photocatalytic degradation of NP10EO was strongly influenced by these parameters. The best conditions for the photocatalytic degradation of NP10EO were obtained. The optimum amount of the photocatalyst used was found to be 0.2 g/L. The photodegradation efficiency of NP10EO increased with the increase of the illumination time. The degradation efficiency is enhanced by increasing reaction temperature and the photodegradation efficiency decreased with an increase in the initial concentration of NP10EO. Analysis of kinetic showed that the amount of surfactant photocatalytic degradation could be fitted into pseudo-second-order model.